Bài 2: Phương trình lượng giác cơ bản

VC

Tìm m để phương trình sau có nghiệm

\(2sin^2x-sinx-m+3=0\)

NL
21 tháng 8 2020 lúc 12:26

Đặt \(sinx=t\Rightarrow-1\le t\le1\)

Pt trở thành: \(2t^2-t-m+3=0\)

\(\Leftrightarrow2t^2-t+3=m\)

Xét \(f\left(t\right)=2t^2-t+3\) trên \(\left[-1;1\right]\)

\(-\frac{b}{2a}=\frac{1}{4}\in\left[-1;1\right]\) ; \(f\left(-1\right)=6\) ; \(f\left(\frac{1}{4}\right)=\frac{23}{8}\) ; \(f\left(1\right)=4\)

\(\Rightarrow\frac{23}{8}\le f\left(t\right)\le6\)

\(\Rightarrow\) Pt đã cho có nghiệm khi và chỉ khi \(\frac{23}{8}\le m\le6\)

Bình luận (0)